2015
DOI: 10.3389/fpubh.2015.00177
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Testimonies: An Ethnographic Study of Emotional Suffering Related to Migration from Mexico to Arizona

Abstract: It is increasingly argued that social and economic inequities poorly affect overall health. One of the means through which these inequities are translated to the body is via negative emotions, which carry known psychological and physiological responses. This paper examines migration-related psychosocial stressors impacting first-generation Mexican immigrants in southern Arizona, and reports on the primary emotional experiences immigrants associate with these stressors. Data were drawn from a qualitative, ethno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
(55 reference statements)
1
23
0
1
Order By: Relevance
“…The United States is home to approximately 11.4 million undocumented immigrants, half of whom are of Latino origin [1,2]. Immigrants, regardless of legal status, face significant stress both during and following migration [3][4][5]. The immigration experience itself has been shown to threaten individual and family well-being due to separation from family, exposure to traumatic events, discrimination, and loss of social status [6].…”
Section: Introductionmentioning
confidence: 99%
“…The United States is home to approximately 11.4 million undocumented immigrants, half of whom are of Latino origin [1,2]. Immigrants, regardless of legal status, face significant stress both during and following migration [3][4][5]. The immigration experience itself has been shown to threaten individual and family well-being due to separation from family, exposure to traumatic events, discrimination, and loss of social status [6].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and Finch () examined the law's effects on Latina/os’ self‐reported health and found that Spanish speakers were more negatively impacted than English speakers. Additionally, Crocker's () qualitative ethnography of Latina/os in Arizona found that the law exacerbated structural inequalities that contributed to heightened psychological and emotional stress among immigrants. These intensified hostile environments are an important component to our study.…”
Section: Background: State Immigration Lawsmentioning
confidence: 99%
“…Tougher immigration enforcement and restrictive policies continue under the new administration, giving rise to greater uncertainty, which may drive more mixed-status households into the shadows (6). Moreover, the daily anxiety of being detained and deported creates an environment of fear and emotional distress for immigrant communities (710). Immigrants' fear of deportation and social stigmatization impede access to health care and make them more vulnerable to chronic illnesses (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the primary family wage earner is deported during Immigration Custom Enforcement's (ICE) removal operations, the remaining family members suffer economic hardships (10, 13). Particularly affected are children of mixed-status households where one or both parents are non-citizens, either undocumented or permanent legal resident, and where one or more children are U.S. citizens (1416).…”
Section: Introductionmentioning
confidence: 99%